Ecranisation of the Artistic Setting of the Dilan he was Dilanku year 1990 Novel by Pidi Baiq and Dilan 1990 Film by Fajar Bustomi - riyana sulaiman (ROLLING, 2022)
There was a reduction in the setting of the film to save on production costs and its impact on the duration of playback, the addition of settings raised in the film to clarify the story and location of the story that is not raised in the novels, and the varied settings changes that appear in the film to customize the flow, message, and dramatization of the story. The ecranization of settings in the novel to the form Of Dilan 1990 film There is a reduction of the 42 section description, the addition of 19 section descriptions, and the material of 20 section descriptions.